An Open-Label, Randomized Trial of Methylphenidate and Atomoxetine Treatment in Adults With ADHD. (January 2017) - Ni, Hsing-Chang; Lin, Yu-Ju; Gau, Susan Shur-Fen; Huang, Hui-Chun; Yang, Li-Kuang
Objective: To directly compare the efficacy of methylphenidate and atomoxetine in improving symptoms, social functions, and quality of life among adults with ADHD.Method: This was an 8-to-10-week, open-label, head-to-head, randomized clinical trial with two treatment arms: immediate-release methylphenidate (IR-methylphenidate; n = 31) and atomoxetine once daily ( n = 32). The outcome measures included ADHD symptom severity, quality of life, and functional impairments.Results: We found a significant reduction in overall ADHD symptoms and improvement in social functions and quality of life for both groups at Weeks 4 to 5 and Weeks 8 to 10. There was no significant difference in the slope of improvements over time except that atomoxetine was superior to IR-methylphenidate in reducing hyperactive/impulsive symptoms at Weeks 4 to 5. There was no significant group difference in the rates of adverse effects.Conclusion: Both IR-methylphenidate and atomoxetine are well tolerated and efficacious in ethnic Chinese adults with ADHD.